Use Rights for Common Pool Resources and Economic Development - Frederik Noack; Marie-Catherine Riekhof; Martin Quaas (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
This paper explores the long–run development of an economy with a traditional sector based on common–pool resource-use, a modern, resource–independent sector with fixed entry costs, and an imperfect capital market. We show theoretically that introducing resource-use regulations increases incomes in the traditional sector and that this can trigger a development process with labor reallocation to the modern sector. Allowing trade of resource-use rights, or distributing resource-use rights unequally, broadens the scope for development.
Keywords: Q28; Q20; O13; O15; O44; 330; natural resources and development; use rights and development; wealth distribution and occupational choice